Optimalisasi UU ITE untuk Menangkal Hoaks selama Pilkada 2024 Sumatera Utara - Tanjung, M. Taufiq Hidayah; Sazali, Hasan (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2025)
This study aims to analyze the implementation of Law No. 11 of 2008 concerning Electronic Information and Transactions (ITE) in preventing the spread of fake news (hoaxes) during the 2024 Regional Election in North Sumatra. It also seeks to identify the obstacles and solutions faced by local governments in optimizing the role of governance communication. A descriptive qualitative approach was employed, using field research methods. Primary data were collected through in-depth interviews. Secondary data were supported by literature sources such as books, journals, and scientific articles. Data analysis utilized a thematic approach to identify key emerging themes. The results of the study indicate that the implementation of the ITE Law plays a significant role in countering the spread of hoaxes, which can influence public opinion and the reputation of regional head candidates. The informants emphasized the need for strict law enforcement, public education on digital literacy, and collaboration between the government, media, and society to minimize the impact of hoaxes. The challenges identified include a lack of trained human resources, low public digital awareness, and limited infrastructure in the regions. Proposed solutions include strengthening digital literacy, establishing special task forces to handle hoaxes, and enhancing collaboration between the government, political parties, and the public. This study recommends optimizing the implementation of the ITE Law through preventive, collaborative, and fair approaches to create a healthy democratic environment during the 2024 Regional Election.